Convex sets strict separation in Hilbert spaces - Ferreira, M. A. M. (2014)
Convex sets separation is very important in convex programming, a very powerful mathematical tool for operations research, management and economics, for example. The target of this work is to present Theorem 3.1 that gives sufficient conditions for the strict separation of convex sets.